The Boundaries of Latino Sport Leadership: How Skin Tone, Ethnicity, and Nationality Construct Baseball's Color Line. Issue 1 (5th December 2016) - McGovern, Jen
Abstract : Ethnoracial minorities constitute a sizeable percentage of the U.S. labor force, but are underrepresented in top management positions. Research examining the leadership gap focuses primarily on blacks and whites without giving ample attention to Latinos, whose experiences differ greatly based on phenotype, birthplace, and citizenship. This research uses an intersectional approach to examine how these categories overlap to influence Latino leadership in Major League Baseball. Using records data and descriptive statistics, the study shows that skin color and nationality influence leadership opportunities more than ethnicity does. Americans from all ethnoracial groups are more likely to lead than foreign‐born individuals. Regardless of ethnicity, white and light‐skinned individuals are more likely to be pitchers, catchers, managers, coaches, and broadcasters while dark‐skinned people are underrepresented in those roles. The data indicate that American‐born and light‐skinned Latinos have experiences similar to their white counterparts while foreign‐born and dark‐skinned Latinos merge into collective blackness. This hierarchal structure reinforces historical racialized meanings about race and points toward a racial classification system where individuals will be sorted based on multiple, overlapping categories.